COMPARISON OF FLAIR AND DWI MRI IMAGES IN ACUTE CEREBRAL ISCHEMIC STROKES - Atalu, Abolfazl; Abbasi, Vahid; Sadeghieh-Ahari, Saeed; Mohammadi, Farnaz (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2025)
Background: Given the significance of the topic in the early identification of stroke symptoms through Magnetic Resonance Imaging (MRI) techniques. Objective: This study aimed to compare the result of fluid-attenuated inversion recovery (FLAIR) and diffusion-weighted imaging (DWI) MRI in the early detection of acute ischemic stroke in patients. Methods: This cross-sectional study was done n 100 patients with stroke who referred to Alavi hospital in Ardabil city during 2019. Demographic information including age, gender, place of residence, level of education was extracted from patient’s file. Finally, MRI of these patients who were imaged through DWI and FLAIR methods was included in the checklist and then analyzed by using independent t-test and chi-2 in SPSS version 21. Results: Among the patients studied, 70% were male, with an average age of 64.38 years. Additionally, 64% of the patients had a history of hypertension, while 39% were diagnosed with diabetes. The comparison of DWI and FLAIR results showed significant differences within the first 24 hours following the stroke event. Conclusion: The results showed that DWI method is better than FLAIR for early detection of stroke.